SPIRIT SACROSANCTUM CONCILIUM. Mendorong Sebuah Liturgi Yang Hidup, Kontekstual, Inkulturatif - Ignasius Ledot (Institut Filsafat dan Teknologi Kreatif Ledalero, 2013)
The reform of the liturgy is to be “marked by the gong of tradition and the spirit of genuine renewal”. This “motto” of liturgical renewal reminds us of the importance of being aware that both tradition and our contemporary situation need to be experienced together in our celebrations. The purpose of the liturgical renewal by the Second Vatican Council, was not renewal for the sake of renewal itself, but rather so that celebrations produced by such reform are meaningful for the active participation of the people of God. To achieve this ideal, judicious considerations need to be taken regarding tradition and contemporary developments. One important fruit of the analysis of the Second Vatican Council is that active participation should become ever wider and deeper in our liturgical celebrations. Participation that is both active and conscious whether physically, together with the whole rich genius of the culture, or spiritually, is a part of the richness of grace for which we should indeed thank God. The presence of Sacrosanctum concilium invites all social levels and classes to participate actively and consciously in sacrificial celebrations and in the Lord’s Supper. Kata-kata kunci: Sacrosanctum Concilium, pembaruan, liturgi, misale, partisipasi, aktif dan sadar, inkulturasi, Gereja, umat Allah, rubrik, kurban, keselamatan.